Future high-resolution and high-cadence observations for unraveling small-scale explosive solar features - Sterling, Alphonse C.; Moore, Ronald L.; Panesar, Navdeep K.; Samanta, Tanmoy; Tiwari, Sanjiv K.; Savage, Sabrina L. (Frontiers in Astronomy and Space Sciences, 2023)
Solar coronal jets are frequently occurring collimated ejections of solar plasma, originating  from magnetically mixed polarity locations on the Sun of size scale comparable to that of a  supergranule. Many, if not most, jets are produced by eruptions of small-scale filaments, or  minifilaments, whose magnetic field reconnects both with itself and also with surrounding coronal  field. There is evidence that minifilament eruptions are a scaled-down version of typical filament  eruptions that produce solar flares and coronal mass ejections (CMEs). Moreover, the magnetic  processes building up to and triggering minifilament eruptions, which is often flux cancelation,  might similarly build up and trigger the larger filaments to erupt. Thus, detailed study of jets will  inform us of the physics leading to, triggering, and driving the larger eruptions. Additionally, such  studies potentially can inform us of smaller-scale jet-like features, such as jetlets and perhaps  some spicules, that might work the same way as jets. We propose a high-resolution (~0.1 pixels),  high-cadence (~5 seconds) EUV-solar-imaging mission for the upcoming decades, that would be  dedicated to observations of features of the solar-jet size scale, and smaller-scale solar features  produced by similar physics. Such a mission could provide invaluable insight into the operation of  larger features such as CMEs that produce significant Space Weather disturbances, and also  smaller-scale features that could be important for coronal heating, solar wind acceleration, and  heliospheric features such as the magnetic switchbacks that are frequently observed in the solar  wind.